Propuesta de un plan estratégico de marketing para el centro Óptico Visual de la ciudad de Loja - Díaz Quezada, Rebeca Elizabeth (2015)
The Visual Optical Center is dedicated to providing visual diagnostic service and marketing of optometric products, is located in the city Loja. After the preparation of this research project where several goals are plated, the same as with the present intention to implement was performed. The objective general was propose a strategic marketing plan that allows possession both the local market and provincial. And as specific targets in the first instance we perform an external analysis of the business, the same as were met by analyzing external factors (economic, political, social, etc), these helped to identify opportunities and threats to which facing the company. In the second objective: to perform an internal analysis of the business, the same as through interviews and surveys to employees and customers came to identify weaknesses and strengths that owns the company. With the results of the various analyzes are able to fulfill the third objective was to conduct a SWOT analysis and perform the SWOT matrix with the mistakes: free entry to market competition, larger competitors locally and Optical GMO, increased substitutes and informal competition;. Opportunities: reducing imports and consumption incentive al domestic product increased demand due to excessive use of technological devices, technological advancement to systematize production and inventories lens;. Strengths: good personal references, competitive price, good business location, product selection, quality products and services;. Weaknesses: not offer promotions to customers, little publicity in the media, lack of training and motivating employees, does not have a slogan that reflects the corporate image. Then with the development of High Impact Matrix was complied fourth objective, where a matrix where the SWOT factors is described in greater incidence was performed, taking and EFE Matrix results the prevalence of threats 2.36donde exists on opportunities, putting in risk as losing their customers. In the Matrix EFI, was 2.38 resulted where there is a predominance of the weaknesses of the threats which puts her at a disadvantage against competitors. As penultimate goal we design a strategic marketing bread objectives, strategies, tactics, they would help to improve sales of products and services sold by the company. The objectives are: To capture new markets by opening a branch in one of the districts of the province of Loja, in an effort to expand market coverage lojano and affirm its position, its value will have to launch an initial cost of $ 3900.00; Customer satisfaction, with staff training seminars on human relationships and improving customer care so the same, they have a value of $ 1500.00; Disseminate local and provincial level of services and products offered by Optical Center Visual and benefits that entails the use of lenses for eye health, have a value of $ 2,863.00 dollars; Projecting the corporate image of Optical Center Visual in all its products, in order to be a competitive company in the lojano market will be worth of $ 620.00; E Encourage and motivate customers to complete the purchase of products and services through promotions offered by the company, will have a value of $ 335.00. Finally it was concluded that the company provides a service and quality products but lack of strategies were unable to reach higher ranks within the local and provincial. That is why it is recommended to consider this proposal in order to solve their problems and achieve sustainable development; the same is budgeted at $ 9218.00 US dollars Americans.